The Role of Russian Federation Government Policy in Addressing the Impacts of Global Climate Change - Heinrich Rakuasa; Philia Christi Latue; Yamres Pakniany (Journal of Selvicoltura Asean, 2024)
Climate change has become a pressing global issue, with vulnerable countries such as the Russian Federation facing significant challenges. This research aims to explore the role of Russian government policies in addressing the impacts of global climate change. The research method used is a literature study that includes data analysis from various reliable sources. The results and discussion highlight that Russia is vulnerable to climate change due to its vast territory and dependence on the fossil fuel industry. Socio-economic impacts such as heat waves, forest fires and permafrost thawing have reinforced the urgency of mitigation and adaptation measures. Recommendations include strengthening climate policies, diversifying energy sources, raising public awareness, international collaboration, and technological innovation. By addressing challenges such as lack of public awareness and limited resources, Russia can play a more proactive role in protecting the environment and creating a sustainable future.